Acceptance of alien queens by the ruby ant Myrmica rubra (Hymenoptera: Formicidae): Gene flow by queen flow - Jouni Sorvari (CZECH ACAD SCI, INST ENTOMOLOGY, 2022)
Social insect colonies, especially of ants, often include several egg-laying queens that are not always closely related to each other. At least in some cases, the ants seem to accept non-related queens into their colonies. Here I test whether the colony queen status (with or without a queen), genetic and geographic differences between source and recipient nests and the average relatedness of the workers in the recipient colony affect the acceptance of alien queens. I used field collected ruby ant Myrmica rubra colonies as a model system. Only the queen status significantly affected the acceptance process. Colonies without queens accepted alien queens more frequently than colonies with a queen. The nests without queens and nest fragments may act as vectors for gene flow by the movement of queens between nests, i.e., queen flow.